Fine-needle aspiration cytology of a cesarean scar endometriosis - Nigam, Jitendra Singh (Tzu Chi Med J, 2017)
Endometriosis is the presence of functioning endometrium outside the basement membrane of the uterine endometrium. It affects women of reproductive age and usually presents as a painful nodule over a period of 3 months to 10 years after surgery. Extrapelvic endometriosis is uncommon and more difficult to diagnose due to its variable presentation and is often confused with other surgical conditions. Fine-needle aspiration cytology (FNAC) is a rapid, cost-effective, and accurate diagnostic tool when making this diagnosis. Wide excision is the treatment of choice for scar endometriosis as well as for recurrent lesions. We present a case of scar endometriosis in a 30-year-old female who had undergone a cesarean section 2 years previously and was diagnosed by FNAC. A later histopathological examination confirmed the cytological diagnosis of scar endometriosis.